2018
DOI: 10.3846/btp.2018.02
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Intrapreneurial Engagement Initiatives and Its Influence on Organisational Survival

Abstract: Employee intrapreneurial engagement is considered to be one of the fundamental initiatives that can help organisations to achieve a sustainable competitive advantage in the midst of economic hardship and stiff competition particularly in a volatile and competitive business environment. The main objective of this study is to examine how employees’ intrapreneurial engagement initiatives would influence organisational survival. Few studies analyse how employee intrapreneurial engagement may foster organisational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…First, part of the human resource management literature calls for bringing humanity back into HRM, and by giving voice to an employee, organizations are humanized [43]. Second, employee participation as an HR practice enables organizations to survive and remain consistent over the long term [44]. The active participation of employees strengthens the organization in the achievement of continuous improvement [45].…”
Section: Introductionmentioning
confidence: 99%
“…First, part of the human resource management literature calls for bringing humanity back into HRM, and by giving voice to an employee, organizations are humanized [43]. Second, employee participation as an HR practice enables organizations to survive and remain consistent over the long term [44]. The active participation of employees strengthens the organization in the achievement of continuous improvement [45].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that frontline professionals across multiple other sectors accepted the ECHO® Networks, as virtual communities of practice, as an innovative new product/service to effect practice change. This research identi ed and expanded on evidence suggesting that public sector organizations could bene t from exploring more intrapreneurial approaches to change/innovation given the adoption and embedding of innovations like the ECHO model™ within CHQHHS (Falola et al, 2018;Guven, 2020;Neessen et al, 2019;Park et al, 2014). The key strategies highlighted by Heinze and Weber (2015) were overlayed to understand and contextualize tactics employed by the project team throughout the implementation of the new business innovation to ensure it was successfully embedded within the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Antoncic & Hisrich, 2003). Employees within these organizations that can be characterized by their motivation to proactively identify and seize opportunities to acquire resources (human and capital) to implement innovations, change, or departures from the status quo are considered intrapreneurs (Altinay, 2004;Falola et al, 2018;Heinze & Weber, 2015;Park, Kim, & Krishna, 2014). The contextual landscape of public healthcare organizations is conducive to fostering cultures where the concept of intrapreneurship can be mobilized by the workforce to innovate and improve the delivery of healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…Without a system, however rustic, suggestions can become a nuisance since each idea can receive a different approach and perhaps the most innovative one is neglected [4]. Most of the researched works do not deal with the use of these systems specifically [5,8,9,10,11,13,14]. Whether due to the lack of openness for a survey at this level or because the tool is not a specific model, but adaptable to each structure and often, even though the organization is not guided by ideas, there is an informal channel to capture these opinions [6,7].…”
Section: Measuring Intrapreneurship At the Individual Level: Development And Validation Of The Employee Intrapreneurship Scale (Eis)mentioning
confidence: 99%
“…In the state of the art, it is evident that intrapreneurship is strategic in order to be competitive and enhance the growth of the companies' innovative capacity [10]. The use of a suggestion program can organize, facilitate control and equity in assessments, reinforcing the role of the intrapreneur [6].…”
Section: Measuring Intrapreneurship At the Individual Level: Development And Validation Of The Employee Intrapreneurship Scale (Eis)mentioning
confidence: 99%